Murder on the Orient Express (2017) [videorecording (DVD)] - Branagh, Kenneth; Bateman, Tom, 1989-; Cruz, Penélope; Dafoe, Willem; Dench, Judi, 1934-; Depp, Johnny; Christie, Agatha, 1890-1976 (20th Century Fox Home Entertainment, 2018)
What starts out as a lavish train ride through Europe quickly unfolds into one of the most stylish, suspenseful and thrilling mysteries ever told. From the novel by best-selling author Agatha Christie, tells the tale of thirteen strangers stranded on a train, where everyone is a suspect. One man must race against time to solve the puzzle before the murderer strikes again.